Ovarian preservation with lateral ovarian transposition in operable Ca cervix: experience at a tertiary care center - Jose, Tony; Singh, Amarinder; Sinha, Pooja; Bidari, Sumit (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The benefits of ovarian preservation during radical surgery for ca cervix in premenopausal patients far outweigh the risk of ovarian disease later. However, adjuvant pelvic radiotherapy damages retained ovaries. Mobilization and transposition of these ovaries during surgery outside the pelvis prevents or reduces radiation damage to these ovaries. A prospective observational study was conducted to objectively study the effect of ovarian preservation with Lateral Ovarian Transposition (LOT) on ovarian function on operated patients of Ca cervix. Methods: All pre-menopausal patients of Ca cervix <45 years, planned for surgery underwent FSH levels to assess ovarian function and were screened for ovarian disease. Eligible patients who consented underwent ovarian retention (OR) with LOT during surgery. Adjuvant treatments as indicated was administered and all patients were followed up at 3, 6 and 12 months after surgery for subjective (symptoms) and objective (FSH) evidence of ovarian failure. Results: LOT could be successfully performed in all patients. Though the mean FSH values did show a rise after surgery, this was more pronounced in patients receiving radiotherapy (RT). Ovarian function continued normally in 63% of all patients with 72% retaining ovarian function when RT was not administered. Hot flashes (HF) and Vaginal dryness(VD) were the most common symptoms but its onset was gradual and symptoms milder compared to surgical menopause. Conclusions: LOT is an oncologicaly safe, technically feasible and reasonably effective procedure for preserving ovarian function during surgical treatment and even after adjuvant RT in Ca Cervix and should be offered to eligible premenopausal patients.